Peran Asuransi BPJS Ketenagakerjaan terhadap Buruh yang Bukan Penerima Upah (BPU) di Tanjung Morawa - Ellysa Pradina; Fauzi Arif Lubis (Universitas Muhammadiyah Surabaya, 2023)
AbstrackÂ BPJS Employment (Social Security Organizing Agency) is a social security program which is the responsibility and obligation of the State to provide certain socio-economic protection and its organizers use an insurance mechanism. In addition, BPJS Employment is only intended for workers. In this social security program there are 2, namely Employment BPJS and Health BPJS, and both of course have different functions. BPJS Ketenagakerjaan is only intended for workers, while BPJS Health is intended for all levels of society. BPJS Ketenagakerjaan has four types of social security programs for workers, namely Work Accident Insurance (JKK), Death Benefits (JK), Old Age Benefits (JHT), and Pension Benefits (JP). In this study the problems that arise from the lack of awareness of the people with the status of non-wage workers (BPU). The points that must be paid attention to by the Tanjung Morawa Employment BPJS institution, especially towards workers who are not wage earners (BPU) because there are still many people with labor status who do not know and lack public understanding of BPJS Employment, there are very many human resources in Tanjung Morawa whose status is daily workers. Freelancers who work do not use work safety guarantees, namely BPJS Ketenagakerjaan. This research is a descriptive qualitative research using primary data in the form of interviews with officers in the general section of the Employment BPJS office and sources from workers whose status is workers who are not wage earners (BPU) and secondary data, namely data obtained from references in the form of journals, writings, and other sources. Based on the results of the study, it was shown that in the role of the Employment BPJS, the Tanjung Morawa Employment BPJS had carried out percentages in the form of outreach to villages with participants attended by workers whose status was casual daily laborers or workers who were not wage earners (BPU). And also many of the workers who are not wage earners (BPU) still don't know what BPJS Employment is and while they are working they only know BPJS Health.Keywords: Program, Social Security. Employment, Workers are not wage earners